2017
DOI: 10.1088/1367-2630/aa78cb
|View full text |Cite
|
Sign up to set email alerts
|

Detecting continuous gravitational waves with superfluid4He

Abstract: Direct detection of gravitational waves is opening a new window onto our universe. Here, we study the sensitivity to continuous-wave strain fields of a kg-scale optomechanical system formed by the acoustic motion of superfluid helium-4 parametrically coupled to a superconducting microwave cavity. This narrowband detection scheme can operate at very high Q-factors, while the resonant frequency is tunable through pressurization of the helium in the 0.1-1.5 kHz range. The detector can therefore be tuned to a vari… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(71 citation statements)
references
References 68 publications
(155 reference statements)
1
70
0
Order By: Relevance
“…For example, the frequency spectrum of a resonator depends on its dimensions and hence knowledge of the precise values of these dimensions is of utmost importance. Cases in which the effects of gravitational fields and acceleration must be considered include those in which the gravitational field is to be measured, such as in proposals for the measurement of gravitational waves with electromagnetic cavity resonators [1][2][3][4][5][6][7] or other extended matter systems [8][9][10][11][12][13][14], tests of GR [15,16] or the expansion of the universe [17,18]. Other situations are those in which the metrological system is significantly accelerated [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the frequency spectrum of a resonator depends on its dimensions and hence knowledge of the precise values of these dimensions is of utmost importance. Cases in which the effects of gravitational fields and acceleration must be considered include those in which the gravitational field is to be measured, such as in proposals for the measurement of gravitational waves with electromagnetic cavity resonators [1][2][3][4][5][6][7] or other extended matter systems [8][9][10][11][12][13][14], tests of GR [15,16] or the expansion of the universe [17,18]. Other situations are those in which the metrological system is significantly accelerated [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…We found that the effect of a gravitational wave on a small scale gravitational wave detector of any type mentioned in the introduction can be mimicked by a system of 10 oscillating spheres or a system of 8 oscillating cylinders. In principle, strains can be mimicked that are several orders larger than the sensitivities claimed by some of the proposals [8,10]. Additionally, the orientation of the polarization plane of the mimicked gravitational waves is known and the local detectors can be oriented so that their signal is maximized.…”
Section: Discussionmentioning
confidence: 99%
“…The dimensions of this detector would be about 50 cm. Therefore, L can be of the order of meters and strains could be mimicked that are up to 3 orders of magnitude larger than the expected sensitivity of the Gen1 detector in [10]. Therefore, the mimicked strains could be used as a tool to experimentally test the proposed detector designs.…”
Section: Signal Amplitudesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case only the mechanical degree of freedom is provided by the fluid, for example, as a density wave or surface wave that detunes the cavity by modulating the overlap between the liquid and the cavity mode. This approach has been used at cryogenic temperatures with superfluid 4 He serving as the liquid [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%